(3QSGdI GdWjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd CcQe Gddg eKhGg gd dC;O ef ZNhGfi ai Cf jgH di ef SeYg bOQ eG Cdbi Ydjg WQakG ef GTLGfi YSGg jJMed Yfi s
(3BNQgG (B:s
(3Ch jfXb GdWjQ cGf GdeQGO bO ZdH ai eRGMc hSjYde GdPjf XGdehG Gi efbdH jfbdHhf JeJ GdQSGdI GdebdHI HQSGdI GdWjQ ddTjN GdQFjS CHj Ydi Hf SjfG hddg GdMeO HdG fgGjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B887s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3eLGejY (B13) s
Keywords: (3GdadSaI hGdefWbs